The Universities - III - Meenan, James (Statistical and Social Inquiry Society of Ireland, 1950)
The limitations of this paper should be made clear at the start. It represents an attempt to bring together the statistics relating to university education in this part of the country and to examine how far they have changed in the last twenty-five years. Apart from the tables published in the annual Statistical Abstract, no figures for all the institutions are generally available; and it is hoped that their collocation may be of some service. It must be confessed that the paper lags far behind the model provided by the reports of the University Grants Committee in Great Britain; but its scope must necessarily be more limited. Not all the ground can be covered; and one can only hope that no essential point has been left unsurveyed. Few activities lend themselves less easily to statistical treatment than university education; and it cannot be claimed that this paper goes further than providing a basis for discussion and, perhaps, a starting point for further inquiry.
Read before the Society, 26 May 1950
Keywords: Analysis of the University sector in Ireland; Irish Univerities; Education in Ireland; 314.15